How Constructive Journalism Helps the Small and Medium Enterprises - Lulu Awanila; Nabila Zummrah Rubbah; Nurul Amalia Rizki (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2021)
UMKM memiliki peran yang penting untuk menopang perekonomian di Indonesia dan merupakan pernggerak pertembuhuhan aktivitas ekonomi nasional.Disisi lain, peran UMKM juga sangat penting karena mampu mengembangkan perdagangan, mengurangi kemiskinan dan membuka lapangan pekerjaan. Namun sayangnya belum banyak UMKM yang mampu mengenalkan produknya kepada masyarakat luas. Untuk itu, dari sinilah peran jurnalisme dibutuhkan untuk membantu para pengusaha menyalurkan hasil usahanya. Untuk menganalisis kami menggunakan metode data dengan mewawancari secara lamgsung beberapa narasumber dibidang jurnalisme dan pengusaha. Penelitian ini telah membuktikan bahwa jurnalisme dapat membantu pengusaha dalam hal disini yang dimaksud adalah UMKM dalam mengembangkan usahanya dan membantu UMKM dalam mencapai tujuannya. MSMEs have an important role to support the economy in Indonesia and are the driving force for the growth of national economic activity. On the other hand, the role of MSMEs is also very important because they are able to develop trade, reduce poverty and create jobs. But unfortunately not many MSMEs are able to introduce their products to the wider community. For this reason, this is where the role of journalism is needed to help entrepreneurs distribute their business results. To analyze we used the data method by directly interviewing several sources in the field of journalism and entrepreneurs. This research has proven that journalism can help entrepreneurs, in this case what is meant here is MSMEs in developing their businesses and helping MSMEs in achieving their goals.